Circulating sCD138 and Some Angiogenesis-Involved Cytokines Help to Anticipate the Disease Progression of Early-Stage B-Cell Chronic Lymphocytic Leukemia (Mediators of Inflammation)
Syndecan-1 (CD138) is a transmembrane heparin sulfate proteoglycan expressed on distinct stages of differentiation of B-lymphoid cells. Its prognostic value in B-cell chronic lymphocytic leukemia (B-CLL) has not been evaluated so far. The serum concentration of sCD138 and some angiogenesis-involved cytokines: vascular endothelial growth factor (VEGF), basis fibroblast growth factor (bFGF), and endostatin were studied in 52 previously untreated patients with B-CLL. We found that bFGF and sCD138 levels were significantly higher in B-CLL patients than in controls. In patients with sCD138 level or endostatin level below the median value the lymphocyte count was higher than in patients with serum level of those cytokines above the median value. In patients with progressive disease bFGF level was significantly higher and sCD138 level significantly lower than in patients with stable one. Moreover, high sCD138 level was associated with longer lymphocyte doubling-free survival, and, on the limit of statistical significance, a high endostatin level was associated with shorter progression-free survival. We conclude that serum sCD138 level is increased in early stage B-CLL patients and may have a positive prognostic value as to the dynamics of the disease.